FORMULATION OF HAIR TONIC COMBINATION OF ETHANOL EXTRACTS OF MORINGA OLEIFERA LAM LEAVES AND FRAGRANT PANDAN (Pandanus Amaryllifolius Roxb) AND ITS ACTIVITY ON HAIR GROWTH IN WHITE RATS - Reski Mulia; Iis Wahyuningsih; Moch Saiful Bachri; Sri Mulyaningsih (Medical Sains : Jurnal Ilmiah Kefarmasian, 2024)
Hair is the crown for everyone because hair functions aside from providing warmth, protection, beauty, and support. Hair loss that can cause baldness is one of the most serious problems for everyone. This study aimed to determine the activity of Hair Tonic combination formulations of kelor leaf ethanol extract (Moringa oleifera Lam.) and ethanol extracts of Fragrant Pandan  leaves (Pandanus amaryllifolius Roxb) on rat hair growth compared to single use. The method began with the maseration process of ethanol extract of kelor leaves and ethanol extract of Fragrant Pandan leaves, characterization of extracts (specific and non-specific parameters), chemical content testing of extracts and formulation of Hair Tonic preparations consisting of F1 (positive control), F2 (6% kelor leaf extract), F3 (6% ethanol pandan extract), F4 (combination of 2% kelor leaf extract with 4% ethanol pandan extract), F5 (3% kelor leaf ethanol extract and 3% ethanol pandan leaf extract), F6 (combination of 4% kelor leaf ethanol extract and 2% ethanol pandan leaf extract). The rat hair growth activity was divided into 8 groups: each rat's back was shaved to a size of 4 × 4 cm, the rats were left for 24 hours and then testing was carried out by spraying each formula, and hair growth was observed for 28 days. ...